Transcriptomic profiling of cumulus cells reveals dysregulated genes and pathways in PCOS-related infertility - Sikiru, Akeem Babatunde; Mat Isa, Nurulfiza; Abass, Kasim Sakran; Adeniran, Muibat Adesola; Egena, Stephen Sunday Acheneje; Akinola, Karimot (Springer Science and Business Media Deutschland GmbH, 2025)
Background: Polycystic ovarian syndrome (PCOS) is a leading cause of infertility and metabolic dysfunction in women, characterized by hyperandrogenism, anovulation, and insulin resistance. Cumulus cells play a crucial role in folliculogenesis and oocyte maturation, necessitating a deeper understanding of their molecular alterations impact in PCOS. Method: This study investigates transcriptomic differences in cumulus cells between PCOS and non-PCOS women using high-throughput RNA sequencing data obtained from the NCBI Gene Expression Omnibus (GEO) database (accession number: GSE277906). The RNA sequencing data from 23 PCOS and 17 non-PCOS women were analyzed to identify differentially expressed genes (DEGs) using R-based computational pipelines. Results: Differential gene expression analysis identified 3245 significantly dysregulated genes, comprising 1723 upregulated and 1522 downregulated genes in PCOS samples. Functional enrichment analysis revealed that key DEGs (CDH5, CLEC4D, and GNAT1) were associated with follicular development, insulin signaling, and immune response. Gene Set Enrichment Analysis (GSEA) further identified dysregulation in metabolic and reproductive pathways, including ribonucleoprotein complex biogenesis and vascular endothelial growth factor (VEGF) signaling. Conclusion: This study highlights that altered gene expression in cumulus cells may impair oocyte competence, potentially influencing fertility outcomes in PCOS patients. GNAT1, previously linked to diabetes, emerged as a novel gene potentially involved in PCOS pathophysiology. However, these findings are derived from a single-center dataset which requires experimental validation. Future studies should incorporate qRT-PCR validation and functional assays in larger and ethically diverse cohorts as means for development of targeted therapeutic interventions to mitigate the reproductive consequences of PCOS.